Clima, disponibilidade hídrica e pobreza na porção mineira da bacia hidrográfica do rio Jequitinhonha - Maciel, Samuel Alves (2021)
Climate variability directly influences the hydric availability of hydrographic basins. Nowadays, this water supply has been altered in larger proportions due to the increase of anthropic activities that have used it in an intense and uncontrolled way. The lack of this resource mainly affects the semi-arid regions, where water scarcity is often associated with poverty conditions. Thus, the general objective of this thesis is to evaluate the relationships among climatological and hydrological aspects and poverty indicators in municipalities belonging to the Minas Gerais portion of the Jequitinhonha River watershed. The study basin is inserted in the East Atlantic hydrographic region, covering part of the northeastern part of the state of Minas Gerais and a small portion of southeastern Bahia. For this research, daily rainfall and fluviometric data made available by the National Water Agency (ANA) from 30 stations were used, 18 for the first variable and 12 for the second. A further 19 stations located in the surroundings of the Minas Gerais portion of the basin were selected for the interpolations. The temperature data were acquired from the ERA-5 reanalysis provided by the European Centre for Medium-Range Weather Forecasts (ECMWF). Seven socioeconomic determinants of poverty were chosen, these being: Water Supply by General Distribution Network, Households living below the Poverty Line or in Poverty Situation, Life Expectancy at Birth, Human Development Index (HDI), Gini Index and GDP per capita, provided by institutes and agencies, referenced in 2010 (last census). After tabulating the data, the following methodological steps were performed: delimitation of the contribution areas of the fluviometric stations, initial statistical analysis of the variables and cleaning of climatic data with the elaboration of the Standardized Precipitation Index (SPI), the Climatological Water Balance (BHC) and the Thornthwaite Climate Classification (1948). Subsequently, the maximum, average and minimum flows were determined, as well as the specific flows and the correlation coefficients between rainfall and flow. Finally, the geoprocessing techniques related to data spatialization were applied, such as the elaboration of choropleth maps, spline interpolation and map overlay. The results showed the identification of rainfall seasonality, with a rainy period from October to March and a dry period from April to September. Four climatic types were identified in the basin: semi-arid, dry sub-humid, sub-humid to humid and humid. As for the average annual specific flow rates, these are higher in rainier regions, such as those near the headwaters of the upper Jequitinhonha and Araçuaí River basins. Towards the semi-arid portion of the middle and lower Jequitinhonha River basin the water availability decreases. The last available station downstream (Jacinto) has an average of 4,8 l/s/km² per year. The overlapping of the maps showed that in general no direct relationship was perceived between the physical scarcity of water and the respective poverty scenarios. For example, even if one is in contributing areas with higher water availability, there are municipalities with poor Human Development Index (HDI). Likewise, in the semi-arid region, with low water supply, there are places with high Life Expectancy at Birth and high percentages of Water Supply by General Distribution Network. In summary, although the unavailability of water somehow influences some aspects of poverty in the Minas Gerais portion of the basin, it is believed that other historical, political, economic and social factors are more influential to underdevelopment than the physical scarcity of water itself.